THE ROLE OF A SPECIALIST IN DEVELOPING LIP-READING SKILLS IN CHILDREN WITH HEARING IMPAIRMENTS. (International journal of artificial intelligence, 2026)
This article comprehensively covers the specific features of educating children with hearing impairments, particularly the essence of lip-reading instruction, as well as the roles of specialists, the stages of the instructional process, and the medical and pedagogical conditions required for effective implementation.